Use of Distribution Network Topological Fractality and Sunburst Charts in the Online Risk Assessment - Leite, Jonatas B. [UNESP]; Mantovani, Jose R. S. [UNESP]; Kezunovic, Mladen (Institute of Electrical and Electronics Engineers (IEEE), 2019)
The integration of outage records, historical weather information and fault management events are used in a risk-based GIS driven proactive management tool. It enables the operator to visualize the hourly risk prediction by the graphical representation of the feeder section with a color to each corresponding risk level. The addition of daily hours to the set of spatial coordinates is well suited to perform online risk mitigation but also increases the visualization complexity. Outputs from the risk assessment must be simple and very informative to promote fast action by control center operators. The simplification step is to use a fractal network approach, which allows the use the box-counting method and the renormalization process where a distribution network is collapsed to one node. This simple node can aggregate information of the whole network by using a circle diagram in form of sunburst chart for dynamic visualization and navigation. The effectively of the designed visualization tool is evaluated under electricity networks from a real-world distribution system.
Keywords: fractality; geographic information systems; power distribution networks; renormalization; sunburst